Metal DIY: Dominasi, Strategi, dan Resistensi - Agustinus Aryo Lukisworo; Oki Rahadianto Sutopo (Jurnal Studi Pemuda, 2017)
This article focus on the resistance practice by the DIY metal agents towards popularization of metal in Yogyakarta. Beside, this article also attempt to elaborate the survival startegy of the metal agents in Yogyakarta to maintain the Do-It-Yourself practice. Regarding to those focus, this article does not treat metal as a single entity, rather as a dynamic and fluid social space. Thus this article utilized a considerably different kind of approach compared to previous study of metal in Indonesia. This article is based on an ethnographic research, which utilized praticipant observation and in-depth interview as data collecting methods. The data collection process was carried out of six months.The findings based on the field research show that the resistance practice of metal agents in Yogyakarta was manifested through discursive and musical consumption practices. Both of these practices were used strategically by the DIY metal agents to establish an imaginary boundary against social agents and the field of populer music. Furthermore, the strategy which used to maintain the DIY practices, represented through DIY metal agents involevement within collective actions by one of indie/DIY community in Yogyakarta. Based on the research findings, it can be explained that the dynamics of the field with regards to the resistance and survival strategy by the DIY metal agents represent an intens relation between individuality and collectivity.